2015
DOI: 10.1007/s00261-014-0343-2
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT as a potential predictor of survival in patient with oesophageal cancer: a preliminary result

Abstract: Pretreatment 18F-FDG PET-CT SUVmax of a primary tumour and the presence of FDG-avid lymph nodes independently predict survival in patients with oesophageal carcinoma which may potentially be used as surrogate markers for prognostic and therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Metabolic parameters of PET images were most frequently used in clinical practice and studies (29,30). Although as shown in previous meta-analysis, MTV and TLG was potentially useful prognostic markers of PFS and OS in patients with ovarian cancer (13,14).…”
Section: Discussionmentioning
confidence: 97%
“…Metabolic parameters of PET images were most frequently used in clinical practice and studies (29,30). Although as shown in previous meta-analysis, MTV and TLG was potentially useful prognostic markers of PFS and OS in patients with ovarian cancer (13,14).…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies investigated the predictive and prognostic role of sequential F-18 FDG PET/CT for metabolic tumor response and survival in LAEC treated preoperatively by CRT and revealed conflicting results [17,18,19,20,21,22,23,24,25,26,27,28]. Most of these studies used the SUV max values for the prediction of metabolic response and survival in LAEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies used the SUV max values for the prediction of metabolic response and survival in LAEC patients. Fathinul Fikri et al [19 ]reported that pretreatment with F-18 FDG PET/CT SUV max of a primary tumor and the presence of FDG-avid lymph nodes independently predict survival in patients with esophageal carcinoma which may potentially be used as surrogate markers of prognostic and therapeutic purposes. Although different threshold values were used, other studies showed that ΔSUV max was associated with survival in LAEC treated preoperatively by CRT [20,21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%